2005
DOI: 10.4049/jimmunol.174.9.5814
|View full text |Cite
|
Sign up to set email alerts
|

Defects in CD8+ Regulatory T Cells in the Lamina Propria of Patients with Inflammatory Bowel Disease

Abstract: Mucosal tolerance is believed to be partly mediated by regulatory T cells. Intestinal epithelial cells (IECs) may play an important role in the generation of such regulatory cells, because they are able to process and present Ag to T cells. Furthermore, we have previously demonstrated that IECs are able to generate regulatory CD8+ T cells in vitro. In the present study, we have analyzed lamina propria (LP) lymphocytes for the presence of such regulatory CD8+ T cells in normal individuals as well as in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
129
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 168 publications
(136 citation statements)
references
References 54 publications
4
129
1
2
Order By: Relevance
“…Human CD8 + T cells from healthy colon biopsies have in vitro suppressive activity. In contrast, CD8 + T cells from colon biopsies affected with IBD lack such in vitro suppressive activity (36). These results therefore suggest an important role for defective CD8 + Treg function in human IBD and may explain the difference between the effects of human and mouse AIRE deficiency on chronic intestinal inflammation.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…Human CD8 + T cells from healthy colon biopsies have in vitro suppressive activity. In contrast, CD8 + T cells from colon biopsies affected with IBD lack such in vitro suppressive activity (36). These results therefore suggest an important role for defective CD8 + Treg function in human IBD and may explain the difference between the effects of human and mouse AIRE deficiency on chronic intestinal inflammation.…”
Section: Discussionmentioning
confidence: 42%
“…Human CD8 + T cells from healthy colon biopsies have in vitro suppressive activity. In contrast, CD8 + T cells from colon biopsies affected with inflammatory bowel disease (IBD) lack such in vitro suppressive activity (36). In mice, CD8 + cells play a crucial role in the induction of intestinal tolerance to orally administered antigens (37).…”
mentioning
confidence: 99%
“…CD8-deficient mice were also more susceptible to relapse of autoimmune arthritis after immunization with self antigens (10), suggesting that regulatory activity of CD8 + T cells might reside in the CD8 + memory pool. CD8 + Treg have also been implicated in the regulation of human autoimmune diseases, including inflammatory bowl disease and MS (11,12).…”
Section: Cd8 + T Cells As Suppressor Cellsmentioning
confidence: 99%
“…In the intestine, two major lymphocyte populations exist: the intraepithelial lymphocytes (IEL) which remain associated with the basolateral membrane of the IECs, and the LPL which localize to the subepithelial lamina propria and are in contact with IECs via basolateral projections through the semi-porous basement membrane 1,2 . Previous studies from our lab suggested that IECs function as antigen-presenting cells (APCs) and, as such, can promote regulatory T-cell responses in the mucosa [3][4][5][6][7][8] . In a reverse interaction, studies by Chen et al suggested that IEL could induce IEC differentiation via the production of keratinocyte growth factor (KGF) 9 .…”
Section: Introductionmentioning
confidence: 99%